2004
DOI: 10.17221/5679-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological survey of rats in rural regions of Croatia

Abstract: 70Synanthropic rodents, particularly those living in close association with man, play a significant role in human health, welfare and economy. It has to be stressed that their arthropod ectoparasites are important vectors of pathogenic microorganisms and they can also be important reservoirs for parasitic zoonoses like trichinellosis and capillariosis. No doubt, the increase in rodent populations can be followed by the increase in zoonotic diseases. Hepatic capillariosis is a zoonosis seldom described in peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 8 publications
4
30
2
1
Order By: Relevance
“…Their ability to act as a vector is greatly enhanced due to their physiological similarities which they share with humans (Kataranovski et al 2010). Hence increased rodent population in an area could be directly related to increased zoonotic diseases in human population (Stojcevic et al 2004). Such importance of rodents had also attracted the attention of WHO experts (WHO 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to act as a vector is greatly enhanced due to their physiological similarities which they share with humans (Kataranovski et al 2010). Hence increased rodent population in an area could be directly related to increased zoonotic diseases in human population (Stojcevic et al 2004). Such importance of rodents had also attracted the attention of WHO experts (WHO 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Three helminth species found during present study i.e. H. diminuta, H. nana and C. hepatica have been reported as zoonotic (Stojcevic et al 2004;Waugh et al 2006;Easterbrook et al 2007;Hancke et al 2011) thus representing a risk to public health. Overall investigation on the effect of these parasitic infections on pathophysiology of the host revealed that rodents may serve as reservoirs of these parasitic infections without having much pathogenic effect on their vital organs, fecundity and enzyme activities.…”
Section: Discussionmentioning
confidence: 54%
“…The finding of C. hepatica eggs in the liver of L. striatus in this study is considered to be of immense public health importance because human C. hepatica infections occur following consumption of food or water loaded or contaminated with embryonated eggs of C. hepatica [20]. Hepatic necrosis, parasitic hepatitis, hepatic fibrosis, persistent fever, hepatomegaly and eosinophilia have been recorded in human infections [21].…”
Section: Discussionmentioning
confidence: 65%